2020
DOI: 10.3390/md18070368
|View full text |Cite
|
Sign up to set email alerts
|

Marine-Derived Macrocyclic Alkaloids (MDMAs): Chemical and Biological Diversity

Abstract: The curiosity and attention that researchers have devoted to alkaloids are due to their bioactivities, structural diversity, and intriguing chemistry. Marine-derived macrocyclic alkaloids (MDMAs) are considered to be a potential source of drugs. Trabectedin, a tetrahydroisoquinoline derivative, has been approved for the treatment of metastatic soft tissue sarcoma and ovarian cancers. MDMAs displayed potent activities that enabled them to be used as anticancer, anti-invasion, antimalarial, antiplasmodial, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 132 publications
(313 reference statements)
2
19
0
Order By: Relevance
“…Manzamine A ( Figure 2 B) was isolated for the first time from the marine sponge Haliclona sp. in 1986 [ 129 ]. Its activity to inhibit the GSK3beta enzyme noncompetitively was later discovered by in vitro studies when it was observed that an increase in the concentration of ATP did not cause a change in its inhibitory activity.…”
Section: Marine Compounds Against Alzheimer’s Disease: From Sea To Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Manzamine A ( Figure 2 B) was isolated for the first time from the marine sponge Haliclona sp. in 1986 [ 129 ]. Its activity to inhibit the GSK3beta enzyme noncompetitively was later discovered by in vitro studies when it was observed that an increase in the concentration of ATP did not cause a change in its inhibitory activity.…”
Section: Marine Compounds Against Alzheimer’s Disease: From Sea To Cellsmentioning
confidence: 99%
“…About 100 manzamine alkaloids have been isolated from more than 16 species of marine sponges belonging to 10 genera ( Amphimedon, Pachypellina, Haliclona, Reniera, Cribochalina, Petrosia, Ircinia, Hyrtios, Acanthostrongylophora, and Xestospongia ) and belonging to five families (Chalinidae, Niphatidae, Petrosiidae, Thorectidae, Irciniidae). These sponges are found in Okinawa, the Philippines, Indonesia, the Red Sea, Italy, South Africa, and Papua New Guinea [ 128 , 129 ]. AlTarabeen and colleages purified seven manzamines (ircinal E, manzamine A, 8-hydroxymanzamine A, manzamine F, manzamine A N-oxide, 3,4-dihydromanzamine A N-oxide, and nakadomarin A) from Acanthostrongylophora ingens collected at Ambon, Indonesia [ 153 ].…”
Section: Isolation Of High-value Molecules With Neuroprotective Effects Against Alzheimer’s Diseasementioning
confidence: 99%
“…Alkaloids are the most well-known cytotoxic compounds of MNPs isolated from sponges (Althagbi et al 2020 ) and have established their superiority among other classes of compounds (Izzati et al 2021 ). A relatively common moiety found is the β-carboline (a tricyclic 9 H -pyrido[3,4-b]indole ring structure), also known as norharman (Cao et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indonesian marine sponges also provide nitrogenous alkaloid compounds besides the exclusive β-carboline group (Althagbi et al 2020 ). Two of the recent ones are haliclocyclamines C ( 11 ) and cyclostellettamines F ( 12 ), which were isolated from Haliclona sp.…”
Section: Discussionmentioning
confidence: 99%
“…The ocean is rich in biodiversity, and many organisms have evolved unique morphological and physiological characteristics to adapt to challenging environments (Conte et al, 2021). Marine organisms further produce marine natural products (MNPs) with chemical diversity and interesting structures, including peptides, terpenoids, steroids, polyphenols, alkaloids, etc., (Sable et al, 2017;Murray et al, 2018;Wu et al, 2018;Carroll et al, 2019;Althagbi et al, 2020;Ermolenko et al, 2020). Currently, thousands of new MNPs are being reported every year (Carroll et al, 2020(Carroll et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%